Institutional determinants of bilateral trade: Taking another look - Aljaz Kuncic (Kiel Institute for the World Economy (IfW), 2012)
This paper examines institutional determinants of bilateral trade in a thorough fashion, paying special attention to the issues of selecting institutional measures (using a new dataset), institutional endogeneity (cleansing the endogenous part) and state of the art gravity trade estimations (controlling for multilateral resistance). In terms of the institutional focus, we emphasize, as de Groot et al. (2004), that institutional distance can be an even more relevant determinant of trade than institutional quality on its own, but correct for the technical and substance shortcomings of the afore mentioned paper. We find that not all institutions matter for trade. The consistent effect is that of the quality of origin and destination country's legal institutions, which both increase trade. In terms of political and economic institutions, only the quality of origin's political institutions and destination's economic institutions increase trade, the latter being most salient. More importantly, we highlight the importance of the effect of institutional distance on trade, showing that economic distance affects trade significantly and negatively, an effect practically impossible to dissipate in any specification. Our conclusion in this research is that countries which are more similar in terms of economic institutions, trade more with each other, and that the quality of legal institutions is always conducive to general trade, but surprisingly does not determine your trade partners. Finally, we show that the use of only one of the proxies generally used by the literature to control for institutional environment can be biased and misleading in terms of what is actually being controlled for.
Keywords: 330